Rozwój gospodarczy Państw Europy Środkowo-Wschodniej w latach 2002-2005 - Mindur, Maciej (Economic Development of Central-Eastern European Countries between 2002 and 2005, 2008)
The article comprises an analysis of economies of eight Central-Eastern European countries between 2002 and 2005. Basic macroeconomic indexes (GDP, unemployment, inflation, total demand, public sector financial deficit, government debt) of particular countries, which joined the European Union in 2004, and average indexes EU-8 and EU-15 are presented. Moreover, development trends of described countries' economies in successive years of the investigated period and their competitiveness assessment are compared. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 151-160